Correlation between Students’ Critical Thinking Ability and Self-Confidence on Junior High School - Malik, Farid Fadhil; Nurdin, Irfan Taufik; Hidayat, Wahyu (IKIP Siliwangi, 2024)
One way to improve students' affective and cognitive aspects is through a mathematics learning approach method at school. Achievement of learning objectives (CPL) is demonstrated by the extent to which students have achieved learning objective competencies through a series of criteria or indicators that can be seen from student achievement or learning outcomes. The method in this research uses a non-experimental correlational quantitative research method carried out on class VII students at one of the MTS in Soreang, Kab. Bandung. The aim of this research is to get an idea of how self-confidence influences critical thinking skills or the relationship between critical thinking skills and self-confidence. The results of this research show that the correlation between students' critical thinking skills and self-confidence has a